Effects of Salicylic Acid and Chitosan Foliar Application on Extract Components and the Antibacterial Activity of Melissa officinalis L. - Negin Safari Kamal Abadi; Naser Mohebalipour *; Mehdi Oraei; Hassan Nourafcan; Assad Assadi (Lorestan University of Medical Sciences, 2022)
Background and Aim: Melissa officinalis L. is a medicinal herb with antibacterial properties. This research was carried out to investigate the effects of the foliar application of salicylic acid (SA) and chitosan (Ch.) on ethanolic extracts components and antibacterial activity of M. officinalisL.in the flowering stage. Materials and Methods: The antibacterial activities of the ethanol extracts were investigated using the agar dilution method, minimal inhibitory concentration (MIC), and minimal bactericidal concentration against five bacteria, i.e. S. aurous, B. subtilis, E. coli, S. enterica and P. mirabilis. Results: The major components were citronellal, Z-Citral, E-Citral, caryophyllene oxide, caryophyllene, linalool, carvacrol, α-Pinene and geraniol. The result showed that distinct concentration of Ch. and SA had remarkable effects on the chemical constituents of M. officinalis L. extract. All the examined bacteria were sensitive to the extracts of M. officinalis L. and antimicrobial activities of extracts against the examined bacteria depending on the concentration of the foliar application. The highest and lowest diameters of inhibition zones of the plant extracts were on S. aurous and P. mirabilis respectively. The MIC values of the extracts ranged from 78.25 ppm to 1250 ppm, whereas the MBC values ranged from 156.5 ppm to 1250 ppm. Conclusion: S. aurous and E. coli were the most sensitive bacteria in Gram-positive bacteria and Gram-negative bacteria respectively. It was also observed that Ch. treatments were more effective on Gram-negative bacteria, while SA treatments were more influential on Gram-positive bacteria